2018
DOI: 10.1038/s41395-018-0414-z
|View full text |Cite
|
Sign up to set email alerts
|

Results of First-Round of Surveillance in Individuals at High-Risk of Pancreatic Cancer from the AISP (Italian Association for the Study of the Pancreas) Registry

Abstract: INTRODUCTION: Surveillance programs on high-risk individuals (HRIs) can detect pre-malignant lesions or early pancreatic cancer (PC). We report the results of the first screening round of the Italian multicenter program supported by the Italian Association for the study of the Pancreas (AISP). METHODS: The multicenter surveillance program included asymptomatic HRIs with familial (FPC) or genetic frailty (GS: BRCA1/2, p16/CDKN2A, STK11/LKB1or PRSS1, muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 20 publications
1
24
0
4
Order By: Relevance
“…4 This is mainly due to the fact that most patients present with advanced disease not amenable to surgical resection, which remains the only potentially curative treatment. 5 Indeed, outside of screening programmes that are currently limited to research protocols conducted on small populations of high-risk individuals, 6,7 the disease is usually diagnosed as a result of signs and symptoms that are often unspecific and unrecognised, possibly determining diagnostic delay. The key question concerning early detection is whether or not it is possible to increase survival by identifying those patients whose complaints and risk factors suggest a diagnosis of PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…4 This is mainly due to the fact that most patients present with advanced disease not amenable to surgical resection, which remains the only potentially curative treatment. 5 Indeed, outside of screening programmes that are currently limited to research protocols conducted on small populations of high-risk individuals, 6,7 the disease is usually diagnosed as a result of signs and symptoms that are often unspecific and unrecognised, possibly determining diagnostic delay. The key question concerning early detection is whether or not it is possible to increase survival by identifying those patients whose complaints and risk factors suggest a diagnosis of PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…The surveillance program workflow has been already reported . At the first scheduled appointment, inclusion and exclusion criteria are considered prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Paiella et al reported data of the first round of surveillance of HRIs in the Italian Association for the Study of the Pancreas Registry. 5 The rate of malignancy in the 187 enrolled HRIs was 2.6%, and age older than 50 years, smoking and having more than two relatives with PDAC were independently associated with detection of premalignant and malignant lesions. Finally, Canto and colleagues 6 investigated the incidence of PDAC in 354 HRIs with a median follow-up of more than five years undergoing surveillance in the CAPS (Cancer of the Pancreas Screening) studies in the United States.…”
mentioning
confidence: 88%